Academic and quantitative literacy in higher education: Relationship with cognate school-leaving subjects - Prince, R. N.; Frith, V.; Steyn, S.; Cliff, A. F. (South African Journal of Higher Education, 2021)
Academic and quantitative literacies (AQL) are essential to success in higher education. These literacies are largely not explicitly taught, but acquired indirectly, mostly through practices in various school subjects. The National Benchmark Tests (NBT) Project assesses students’ AQL competencies to assist in identifying students who need support, with placement into appropriate programmes and with curriculum development. We analyse the performance on the NBT AQL test of students who took the school-leaving examinations in Mathematics, Mathematical Literacy, English Home Language and English First Additional Language. We use the subject choice as a representation of the level of a candidate’s quantitative competence and language proficiency respectively, and investigate the relative contributions made by these subject choices to a student’s AQL. Students who paired Mathematics with English as Home Language subject had the statistically significant highest mean AQL score and those who took both English First Additional Language and Mathematical Literacy had the lowest. Language competence has a stronger effect than mathematical competence on AQL. Students who took the subject combination Mathematics and English Home Language at school are better prepared for the academic demands of higher education than their counterparts who took the alternate subjects. Treating these subjects as equivalent to English Home Language and Mathematics for admissions purposes ignores the differences in preparedness of these students.